Potensi Pengembangan Masjid Dalam Islam Untuk Pemberdayaan Ekonomi Masyarakat (Penelitian Masjid Darussalam Kota Wisata) - Eliyawati, Rini; Muti, Ahmad; Rochim, Abdul (Journal of Student Development Informatics Management (JoSDIM), 2023)
This study aims to determine the potential for developing mosques for community economic empowerment and to find out the response of the community around the Darussalam mosque to the economic activities carried out by the mosque. This study uses a qualitative method with a descriptive approach. The data testing technique used is observation and interviews. The data analysis technique used in data collection and after data collection was completed used Miles and Huberman's interactive model in the form of data reduction, data presentation and drawing conclusions. The potential for developing mosques in Islam to empower the community's economy is a priority to improve the community's economy, therefore in the future after the completion of mosque construction is completed it is necessary for mosque management to optimize the function of mosques as a booster for community economic empowerment in the economic sector, special guidance and training for business actors around the mosque. The human resources of Takmir Darussalam Mosque, a tourist city in implementing the potential for community economic empowerment, have qualified qualities in realizing and producing policies for community economic empowerment.